1979
DOI: 10.1093/geronj/34.5.687
|View full text |Cite
|
Sign up to set email alerts
|

Health in Old Age: How Do Physicians' Ratings and Self-ratings Compare ?

Abstract: The present study was designed to provide information on the relationship between self-reports of health and physicians' ratings in an aged sample, and to determine how both of these measures of health relate to longevity. Subjects were 69 survivors (median age = 84.25 years) of a sample of aged twins who had been followed longitudinally since 1947 to 1949. Self-reports of health were found to be significantly correlated with ratings assigned by a physician on the basis of medical records. Both types of measur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
132
1
2

Year Published

1988
1988
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 357 publications
(141 citation statements)
references
References 0 publications
6
132
1
2
Order By: Relevance
“…Several studies have reported that the existence of diseases is an important risk factor for death and this factor has been consistently found to be associated with self-rated health (Friedsam and Martin 1963;LaRue et al 1979;Mihara et al 1983). People with a larger number of comorbidities may have more functional limitations, which is an important factor for poor selfrated health (Hays et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported that the existence of diseases is an important risk factor for death and this factor has been consistently found to be associated with self-rated health (Friedsam and Martin 1963;LaRue et al 1979;Mihara et al 1983). People with a larger number of comorbidities may have more functional limitations, which is an important factor for poor selfrated health (Hays et al 1996).…”
Section: Discussionmentioning
confidence: 99%
“…While 9 scale scores can be produced, recent research suggests that these scores can be reduced to 3 reliable dimensions: physical disability, psychological disability, and pain (13). The AIMS scores have been standardized to range from 0 (low level of disability) to 10 (high level of disability), Various psychosocial measures were also obtained, including daily stress (14,15), morale (16), social support (17), global satisfaction with health care (18,19), and selfrated health status (i.e., excellent, good, fair, or poor) (20)(21)(22). Finally, self-reported compliance with taking medications was assessed; when asked in a nonthreatening manner, accurate answers can be obtained (23).…”
Section: Methodsmentioning
confidence: 99%
“…Since health satisfaction is the only indicator that is available for the entire survey period, all comparisons are necessarily based on subsamples of survey years. Additionally, studies by Nagi (1969), Maddox and Douglas (1973), LaRue et al (1979), andFerraro (1980) are cited by Sammartino (1987), and find that self-reported health status is highly correlated with medically determined health status. Research by Mossey and Shapiro (1982) even found that self-reported poor health was a slightly better predictor of subsequent mortality than objectively determined health status.…”
mentioning
confidence: 99%